Cold-adapted Yeasts Biodiversity, Adaptation Strategies and Biotechnological Significance - Buzzini, Pietro; Margesin, Rosa.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Yeasts are a versatile group of eukaryotic microorganisms, exhibiting heterogeneous nutritional profiles and an extraordinary ability to survive in a wide range of natural and man-associated ecosystems, including cold habitats. Cold-adapted yeasts inhabit numerous low-temperature environments where they are subjected to seasonal or permanent cold conditions. Hence, they have evolved a number of adaptation strategies with regard to growth and reproduction, metabolic activities, survival and protection. Due to their distinctive ability to thrive successfully at low and even subzero temperatures, cold-adapted yeasts are increasingly attracting attention in basic science and industry for their enormous biotechnological potential. This book presents our current understanding of the diversity and ecology of cold-adapted yeasts in worldwide cold ecosystems, their adaptation strategies, and their biotechnological significance. Special emphasis is placed on the exploitation of cold-adapted yeasts as a source of cold-active enzymes and biopolymers, as well as their benefits for food microbiology, bioremediation and biocontrol. Further, aspects of food biodeterioration are considered.
Cold-Adapted Yeasts: a Lesson from the Cold and a Challenge for the XXI Century -- Methods for the Isolation and Investigation of the Diversity of Cold-Adapted Yeasts and their ex situ Preservation in Worldwide Collections -- Cold-Adapted Yeasts in Arctic Habitats -- Cold-Adapted Yeasts in Antarctic Deserts -- Cold-adapted yeasts in Alpine and Apennine glaciers -- Cold-Adapted Yeasts in Patagonian Habitats -- Cold-Adapted Yeasts in Deep-Sea Environments -- Black Yeasts in Cold Habitats -- Production of Pigments and Photo-Protective Compounds by Cold-Adapted Yeasts -- Changes in Lipids Composition and Fluidity of Yeast Plasma Membrane as Response to Cold -- Cold-Shock Response and Adaptation to Near-Freezing Temperature in Cold-Adapted Yeasts -- Production of Antifreeze Proteins by Cold-Adapted Yeasts -- Role of Sterol Metabolism and Endoplasmic-Reticulum-Associated Degradation (ERAD) of Proteins in Cold Adaptation of Yeasts -- Subzero Activity of Cold-Adapted Yeasts -- Fundamentals of Cold-Active Enzymes -- Cold-Active Yeast Lipases: Recent Issues and Future Prospects -- Miscellaneous Cold-Active Yeast Enzymes of Industrial Importance -- Production of Polymers and other Compounds of Industrial Importance by Cold-Adapted Yeasts -- Low-Temperature Production of Wine, Beer and Distillates using Cold-Adapted Yeasts -- Cold-Adapted Yeasts as Biocontrol Agents: Biodiversity, Adaptation Strategies and Biocontrol Potential -- Bioremediation and Biodegradation of Hydrocarbons by Cold-Adapted Yeasts -- Heterologous Expression of Proteins from Cold-Adapted Yeasts in Suitable Hosts: Methods and Applications -- Food Spoilage by Cold-adapted Yeasts.
Keywords: Life sciences; Microbiology; Enzymes; Microbial ecology; Life Sciences; Microbiology; Microbial Ecology; Applied Microbiology; Enzymology